Sistem Informasi Akademik pada SMAN 1 Banyuasin II Menggunakan Metode Rapid Application Development - Asrafli A; Gusmelia Testiana; Muhammad Leandry Dalafranka (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
SMAN 1 Banyuasin II is a senior high school located in South Sumatra Province, Indonesia. The school has experienced difficulties in managing academic information, including student and teacher data, class schedules, classroom data, and important school announcements. The purpose of this study is to develop an Academic Information System (SIAKAD) for SMAN 1 Banyuasin II to assist the school in managing academic data more efficiently. The system was developed using the PHP programming language and MySQL as the database management system. The system development methodology employed is Rapid Application Development (RAD), which consists of three stages: requirements planning, system design, and implementation. The resulting Academic Information System is expected to facilitate SMAN 1 Banyuasin II in addressing various academic management challenges within the school.